Determination of element weight for the purpose of prioritization of intersection collision correction - S. I. Evtushenko; R. V. Ostashev (Vestnik MGSU)
Introduction. It is proposed to optimize the time of highly qualified engineers working with a building information model (BIM) during the correction of intersection collisions due to mathematical determination of importance of an element in intersection collisions.Materials and methods. The method of frequency analysis is taken as a basis, using the quality coefficient of BIM. The quality coefficient of BIM is determined based on the data about the BIM itself: number of elements, objects and collisions. The calculated coefficients influence the results obtained using the frequency analysis method. As a result, unique values of importance weights for BIM elements are obtained.Results. The weights of the elements found during the study are sorted in descending order, the first 20 % of the elements with the highest weight are the load-bearing structures, indicating that fixing collisions involving them should be a priority. The priority of correcting collisions involving other non-bearing elements of the BIM can be determined by assigning weights to them based on the elements involved in collisions.Conclusions. The results of the study will help to assign priority to the intersection collisions found. This, in turn, will allow highly qualified engineers to fix the most important intersection collisions in a priority order, thereby using their time more efficiently. The resulting element weights can be applied by exporting the collisions found in the project to a tabular data format. Using tabular editors and pivot table functions, you can assign weights to elements and sort collisions.